A Diaphragmatic Hernia and Pericardial Rupture Caused by Blunt Injury of the Chest: A Case Review. Issue 5 (September 2018) - Gao, Ru; Jia, Donghui; Zhao, Huimin; WeiWei, Zhang; Yangming, Wang Frank
Abstract : Blunt traumatic diaphragmatic hernias are most commonly seen in combination with other injuries. Right diaphragmatic ruptures with serious pericardium ruptures are relatively rare. The diagnosis of diaphragmatic hernias is not difficult; however, prior to surgery, it is difficult to judge whether pericardium damage has occurred, particularly on the right side. This injury may occur in a critical pathological state in which cardiac tissue is outside the pericardium due to the pericardial defect. Severe hemodynamic disorders or even death may occur if the patient's condition is not diagnosed and treated in a timely manner. The transportation of patients with severe trauma must be performed with extreme caution. It is necessary to weigh a wide range of differential diagnoses in a serious and thorough initial investigation.